2007
DOI: 10.1897/06-272r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes on developing zebrafish (Danio Rerio) embryos

Abstract: The impact of carbon nanotubes (CNTs) on the aquatic environment was investigated by examining the properties of raw CNTs under several environmental conditions and using developing zebrafish (Danio rerio) embryos. The agglomerate size for single-walled CNTs (SWCNTs) was significantly larger at pH 11 or greater and was stable at temperatures from 4 to 40 degrees C and salinities from 0 to 30 ppt. Exposure to SWCNTs induced a significant hatching delay in zebrafish embryos between 52 to 72 h postfertilization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
255
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(277 citation statements)
references
References 41 publications
17
255
1
4
Order By: Relevance
“…Wang et al (2016) found that bioaccumulation of MWCNTs was greater than that of SWCNTs and that embryos treated with SWCNTs presented severe malformations whereas embryos treated with MWCNTs presented normal development. In addition, Cheng et al (2007) and (Girardi et al 2017) reported a delay in the hatching rate of zebrafish embryos incubated with SWCNTs in a concentrationdependent manner. In contrast, working with a wide CNT concentration range that included the concentrations used by Cheng and Girardi, Bayat et al (2015) found no effects.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 97%
See 2 more Smart Citations
“…Wang et al (2016) found that bioaccumulation of MWCNTs was greater than that of SWCNTs and that embryos treated with SWCNTs presented severe malformations whereas embryos treated with MWCNTs presented normal development. In addition, Cheng et al (2007) and (Girardi et al 2017) reported a delay in the hatching rate of zebrafish embryos incubated with SWCNTs in a concentrationdependent manner. In contrast, working with a wide CNT concentration range that included the concentrations used by Cheng and Girardi, Bayat et al (2015) found no effects.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 97%
“…Table 1 describes the different functionalization and toxicological assays carried out in each CNT. Cheng et al (2007) described a delay in the hatching rate of zebrafish embryos incubated with SWCNTs and MWCNTs, with more marked effects by SWCNTs. Wang et al (2016) found that bioaccumulation of MWCNTs was greater than that of SWCNTs and that embryos treated with SWCNTs presented severe malformations whereas embryos treated with MWCNTs presented normal development.…”
Section: Nanoparticles Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is feasible to select toxicological endpoints to find the genes that may be involved in toxicant exposure. Recently, zebrafish embryos have been employed for rapid and high-throughout screening of compounds for developmental toxicity and mechanisms of toxicant exposure, including β-naphthoflavone (Voelker et al, 2007), polybrominated diphenyl ethers (Lema et al, 2007), algal toxins (Berry et al, 2007), dioxins (Bello et al, 2004), polycyclic aromatic hydrocarbons (Incardona et al, 2005), pesticides , heavy metals (Chan and Cheng, 2003;Linbo et al, 2006) and carbon nanotubes (Cheng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In such species it has been demonstrated that CNTs do not interfere with proper embryonic development, and the observed hatching delay might be ascribed to Ni and Co contaminants, rather than the CNTs themselves. 17 Despite the advantages of the zebrafish model, fish development and embryo morphology differ from that of mammals, and findings for one class cannot be automatically translated to the other. To our knowledge, no studies have been so far performed on the effects of CNTs on mammalian embryonic development, despite the high potential clinical and social relevance of this end point.…”
mentioning
confidence: 99%